Randomized control trial of a childhood obesity prevention family-based program: “Abriendo Caminos” and effects on BMI - Teran-Garcia, Margarita; Hammons, Amber J.; Olvera, Norma; Greder, Kimberly; Plaza-Delrestre, Maria; Andrade, Flavia Cristina Drumond; Fiese, Barbara; Wiley, Angela R. (Frontiers in Pediatrics, 2023)
Background. Hispanic individuals are at increased risk for obesity and other chronic health conditions. This article evaluates the effect of a family-based, childhood obesity primary prevention intervention in a community setting. Methods: A multi-site, randomized controlled trial community program with assessments at pre (T0), post-program (T1), and 6-months post-program (T2). Participating families were recruited from five sites. Only families of Mexican or Puerto Rican heritage with a least one child between 6 to 18 years were included in the study, without weight restrictions. Families were randomized to the intervention and control arms. Intervention families received six-2 hr weekly workshops. Control families received printed generic nutrition and wellness information. Heights and weights were measured at the 3-time points to calculate BMI z-scores, BMI-percentiles, and weight status using age- and sex-specific growth charts, according to the CDC guidelines. Results: There were no differences in BMI-z scores between children in the intervention (n=239) and control groups (n=187) at T0. BMI z-scores decreased in the intervention group (-0.03, 95% CI -0.066, -0.003, p= 0.032) at T1, but not in the control group at T1. Changes in BMI z-scores were not statistically significant at T2. Conclusion: The Abriendo Caminos intervention effectively prevented unhealthy weight gain in Hispanic children in the short-term, but not at 6-months post-intervention. Younger children and girls benefited more from the program at 6-months post-intervention. Additional efforts are needed to sustain long-term changes. Culturally-tailored programs can provide families with the knowledge to produce short-term changes and a potential pathway for sustainable changes in implementing healthy behaviors.